2000
DOI: 10.1177/135676670000600305
|View full text |Cite
|
Sign up to set email alerts
|

Hosting the international travel media — A review of the Australian Tourist Commission’s visiting journalist programme

Abstract: Hosting the international travel media provides many benefits to individual tourism organisations and entire destinations. Various national tourist organisations (NTOs) have developed visiting journalist programmes to entice the media to visit a destination and maximise the publicity that can be gained. Unfortunately, there is also much scope for a mismatch of expectations between the destination and media. This paper initially examines the four main issues of understanding travel journalists, recognising diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…'Hosting the international media provides many benefits to individual tourism organisations and entire destinations', according to Mackellar and Fenton. 16 'Although hosting international journalists is seen as a cost effective promotional activity', some DMOs question the qualitative and quantitative results of such a programme. 17 Problems in meeting journalist expectations, the provision of quid pro quo services and the lack of control over the finished product and desired image are just some of the negative elements associated with conducting a media tour programme, according to these authors.…”
Section: Press Kitsmentioning
confidence: 99%
“…'Hosting the international media provides many benefits to individual tourism organisations and entire destinations', according to Mackellar and Fenton. 16 'Although hosting international journalists is seen as a cost effective promotional activity', some DMOs question the qualitative and quantitative results of such a programme. 17 Problems in meeting journalist expectations, the provision of quid pro quo services and the lack of control over the finished product and desired image are just some of the negative elements associated with conducting a media tour programme, according to these authors.…”
Section: Press Kitsmentioning
confidence: 99%
“…It could be argued that some countriesperhaps the more powerful and wealthier ones -are more likely to offer such 'familiarisation' trips which are common in travel journalism. For example, Australia has a well-funded visiting journalists' program, which tries to target countries from which Australia aims to receive tourists (Mackellar and Fenton, 2000). This may be to a significant degree influencing the story selections of various countries' newspapers.…”
Section: Discussionmentioning
confidence: 99%
“…Jones (2001) likewise found that the coverage of the 1999 Rugby World Cup did not allow for any incidental coverage of the region's tourism assets. Even when the destination is featured, unless specific arrangements are made, tourism planners usually do not have any control over what is shown of the destination (Mackellar and Fenton, 2000). Whereas advertising messages can be manipulated in order to convey the message that the advertisers would like the audience to receive and the quality and quantity of the message can be controlled, a destination manager may have no control over the messages and the images conveyed of the destination by event commentators.…”
Section: Literature Reviewmentioning
confidence: 96%